Why emotions matter for successful school leadership - Baidrakhmanov, D. (Opción, 2019)
In this study, I shall argue that emotions are main issues in improving students’ learning, including in crisis situations, understanding intrapersonal and interpersonal skills of teachers and effective teaching, and achieving school success via the study and generalization of pedagogical experience on the research problem, conceptualization of educational practice. As a result, governments can give attention to oblige principals to teach, as this helps students to admire their leadership and to aspire to be like them. In conclusion, emotions, self-understanding and management of emotions, trust, and job satisfaction were important features of successful school leadership.